Impact of Misting Systems on Local Particulate Matter (PM) Levels - William L. Knight; Matthew P. Fraser; Pierre Herckes (Aerosol and Air Quality Research)
Abstract In hot, arid environments, many outdoor spaces are cooled by misting systems. These systems spray a fine mist of water droplets that cool down the surrounding air through the endothermic evaporation process. As water sources often contain dissolved minerals, the evaporating droplet may leave an airborne particulate matter (PM) residue. Currently there is no information available on the impact of misting systems on localized PM concentrations. In this study, PM concentrations are found to increase by a factor of 8 from ambient levels in the vicinity of a residential misting system in controlled experiments. These experiments show PM concentrations decrease with increasing distance from misting systems. Chemical data reveal that chloride and magnesium ions may be used locally as tracers of particles from misting systems as chloride may be subject to atmospheric transformation. The average chloride concentration was 71 µg m−3 in samples collected while the misting system was operational and below the detection limit (< 8.2 µg m−3) in samples collected when the misting system was off. The average magnesium concentration was 11.7 µg m−3 in samples when misting system was on and 0.23 µg m−3 in samples when misting system was off. Ambient measurements of PM10 in public places cooled by misting ranged from 102 ± 10 µg m−3 to 1470 ± 150 µg m−3, and PM2.5 ranged from 95 ± 10 µg m−3 to 990 ± 100 µg m−3. Calculations suggest that misting systems could potentially emit PM quantities on the order of a gram per hour in the respirable particle size range.